Research Progresses and Challenges of Flexible Zinc Battery - Xu, Yunfei; Xu, Xin; Guo, Mei; Zhang, Guoxin; Wang, Yaqun (Frontiers in Chemistry, 2022)
Flexible zinc batteries have great potential in wearable electronic devices due to their high safety, low cost, and environmental friendliness. In the past few years, a great deal of work on flexible zinc batteries has been reported, with exciting results. Therefore, many solutions have been proposed in electrode design and electrolyte preparation to ensure the desired flexibility without sacrificing the capacity. This paper reviews the recent progress of flexible zinc batteries. We discuss the differences between various anode materials, cathode materials, and electrolytes, then the difference of electrode preparation methods of active materials on flexible substrates and its influence on the performance of the battery were discussed. Finally, the challenges and future research trends of flexible zinc batteries in capacity and mechanical properties are pointed out.